PI3K/Akt cooperates with oncogenic Notch by inducing nitric oxide-dependent inflammation - Villegas, Santiago Nahuel (2018)
The PI3K/Akt signaling pathway, Notch, and other oncogenes cooperate in the induction of aggressive cancers. Elucidating how the PI3K/Akt pathway facilitates tumorigenesis by other oncogenes may offer opportunities to develop drugs with fewer side effects than those currently available. Here, using an unbiased in vivo chemical genetic screen in Drosophila, we identified compounds that inhibit the activity of proinflammatory enzymes nitric oxide synthase (NOS) and lipoxygenase (LOX) as selective suppressors of Notch-PI3K/Akt cooperative oncogenesis. Tumor silencing of NOS and LOX signaling mirrored the antitumor effect of the hit compounds, demonstrating their participation in Notch-PI3K/Akt-induced tumorigenesis. Oncogenic PI3K/Akt signaling triggered inflammation and immunosuppression via aberrant NOS expression. Accordingly, activated Notch tumorigenesis was fueled by hampering the immune response or by NOS overexpression to mimic a protumorigenic environment. Our lead compound, the LOX inhibitor BW B70C, also selectively killed human leukemic cells by dampening the NOTCH1-PI3K/AKT-eNOS axis.